Design and development of a compact wideband C-shaped patch antenna for UHF RFID tag - Bashri, M. S. R.; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A. (Maxwell Scientific Organization, 2012, 2013)
A compact low profile patch antenna for Ultra-High Frequency (UHF) Radio Frequency Identification (RFID) tag for metallic applications is presented in this research study. By employing two gap-coupled C-shaped patches, wide half-power impedance bandwidth (RL ≥3 dB) of 152 MHz is achieved for universal application UHF (860-960 MHz) RFID. Moreover, the proposed patch antenna exhibits planar profile which eliminates the need for cross and multi-layered construction thus resulting in ease of fabrication and reduced cost. The proposed antenna design is simulated using Finite Element Method based software. Reported simulations results demonstrate satisfactory performance when the antenna is mounted on various sizes of metal plate.